Antecedents and Consequence of Information Adoption of Sariayu Skincare Prospects - Hasanah, Fauziyyah Ummul; Ernawadi, Yadi (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2024)
This study's goal is to investigate the potential antecedent and consequential effects of Sariayu face mask information adoption by creating a conceptual model of hypotheses that takes into account a wide range of potential contributing variables. The study explores the variables that influence the credibility and utility of EWOM as well as the reasons why buyers could use it. This survey had 140 participants who are potential customers of Sariayu face masks. The data were obtained using a one-shot or cross-sectional approach. Testing for convergent validity, discriminant validity, and composite reliability have all been successfully completed by the instrument. The data analysis method employed in this study was SmartPLS version 3.0 for structural equation modeling, or SEM. Fifteen out of the eight conjectures put up had actual evidence to back them up. Based on the research findings, perceived persuasiveness, eWOM usefulness, and eWOM credibility are all positively impacted by perceived informativeness, and eWOM usefulness positively impacts information adoption. Purchase intention benefits from the uptake of information. In order to establish strategies relevant to enhancing the quality of these features, the study's results are anticipated to be beneficial for future research and assessment management in the beauty industry.